The Influence of Respondent Characteristics and Different Areas on Small-Scale Fisherman Household Income of Urban Coastal Areas in Pare-Pare City, South Sulawesi - Abd. Rahim; Diah Retno Dwi Hastuti; Dita Pradipta; Nurbaya Bustanul; Nur Azizah (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2018)
Traditional fishermen are small-scale fisheries with small-scale catches. They are commonly found in coastal areas and become one of the main income source of coastal communities in developing countries. They use simple fishing gear and small boats in fishing, such as outboard motor and non-powered motor. The changing of seasons (arrest and famine) in Makassar Strait Waters Bordered which is directly to the West coastal area of Pare-Pare City of South Sulawesi Province Indonesia result in the change of the catch and income production of the catching business. That affects the change of household income, especially the small-scale fishermen outboard motor. The multiple regression econometrics analysis method with independent variable estimation model qualitative was applied. The census technique was used in this study with the total of 42 respondents. The findings indicate that the age as the characteristics of the fisherman respondents and the difference of residence areas have an effect on the change of household income of small-scale fisherman. Meanwhile the education, family dependent, and the experience of going to sea do not affect the household income. The productive fishermen has a better physical ability to make an optimal capture for the welfare of their family in meeting the needs in their household.  JEL Classification:  D19, Q18, Q22